Global trends of bibliotherapy and mental health research based on bibliometric analysis - Muthmainnah Aufaa Hamzah; Cecep Ibrahim; Asrul Jaya; La Ode Herman (Berkala Ilmu Perpustakaan dan Informasi, 2026)
Introduction. Bibliotherapy is a therapy practice that uses reading materials to assist people in overcoming mental health issues. The purpose of this study is to identify publication patterns, prominent actors, and prevalent themes in the bibliotherapy and mental health literature. Research Methods. This study employs a bibliometric approach, with data drawn from the Scopus database. The search was conducted using the keywords bibliotherapy and mental health between 2005 and 2025, resulting in 219 documents evaluated. Data Analysis. The analysis covers annual contributions, nations, institutions, authors, journals, and keywords. Data visualization was carried out using VOSviewer to map collaborative networks and theme clusters of bibliotherapy research globally. Results. The findings indicate that while issues like psychological well-being, patient participation, and positive psychology-based techniques are still comparatively infrequently investigated, the themes of bibliotherapy, cognitive-behavioral therapy, depression, and anxiety dominate publications. Conclusions. This analysis verifies the dominance of clinical topics in bibliotherapy research and demonstrates a research vacuum in welfare issues and the broader context of application. Further research is proposed to examine the range of ways and broaden the keywords in order to make the development of bibliotherapy science more comprehensive and useful.